Pengembangan Perangkat Pembelajaran PBM Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis - Siagian, Meryance V (TIN: Terapan Informatika Nusantara, 2021)
This study aims to determine: 1) the validity, practicality and effectiveness of the developed problem-based learning model-oriented learning tools, 2) the improvement of mathematical problem-solving abilities by using the developed problem-based learning model-oriented learning tools, 3) the student's answer process in solve mathematical problem solving through the developed learning model oriented problem-based learning tools. This research is a development research with the Thiagarajan, Semmel, and Semmel development models. The subjects in this study were students of class VII SMP Negeri 13 Medan. From the results of trial I and trial II obtained: 1) the learning device developed meets the valid criteria; learning tools developed meet practical criteria; learning tools developed meet the criteria for being effective; 2) there is an increase in the ability to solve mathematical problems using the developed learning tools; 3) the student's answer process in trial II was better than trial I.